Low expression of the ST6GAL2 and CD248 genes as an unfavorable prognostic marker of oral squamous cell carcinoma - I. K. Fedorova; E. S. Kolegova; E. A. Prostakishina; T. D. Dampilova; M. R. Patysheva; P. S. Yamshchikov; E. V. Denisov; E. L. Choynzonov; D. E. Kulbakin (Опухоли головы и шеи, 2024)
Introduction. Squamous cell carcinoma (SCC) of the oral cavity is an aggressive and rapidly progressing disease. The tendency to progression of the tumor process is due to the clinical and pathological characteristics of the patient and the biological characteristics of the tumor. molecular and genetic disorders related with transcriptome level play an important role in tumor progression, which can be used in predicting the outcome of the disease.   Aim. To identify markers for assessing the risk of the SCC progression.   Materials and methods. Based on the data of the Cancer genome Atlas database, a bioinformatic search for genes associated with the progression of SCC was performed (11 genes were selected). Then we performed a retrospective analysis of clinical data and histological material from 38 patients with SCC treated at the Scientific Research Institute of Oncology of the Tomsk National Research medical Center of the Russian Academy of Sciences from 2018 to 2021. Fixed samples of tumor tissue were examined. The level of gene expression was determined by real-time quantitative polymerase chain reaction.   Results. It was shown that decrease in the ST6GAL2 matrix RNA level is associated with presence of lymphogenic metastases and decrease in the CD248 matrix RNA level is associated with the occurrence of relapses.   Conclusion. Expression level of the ST6GAL2 and CD248 genes can be used as predictors of an unfavorable prognosis of SCC.